The Effect of Shade and Thickness on the Depth of Cure of Bulk-Fill Composites with Different Viscosities - Maryam Novin Rooz; Atefeh Yousefi Jordehi (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: In an attempt to enhance and simplify the restoration process, a new class of composite resins, called the bulk fill composite resins have been introduced. It is claimed that a depth of cure (DOC) of 4 mm can be achieved without affecting the properties of this material. Purpose: The purpose of this study was to investigate the effect of different shades, thicknesses, and viscosities on the DOC of bulk-fill composites. Materials and Method: In this experimental study, four bulk-fill composites [Filtek™ Bulk Fill Flowable (FBF), FiltekTM Bulk Fill posterior (FBP), Tetric® N-Flow Bulk Fill (TNF), Tetric® N-Ceram Bulk Fill (TNC)] and a conventional composite, Filtek™ Z250 XT Universal (FZ) were evaluated. The samples (n=5) were made using two different shades (light and dark), thicknesses (2 and 4mm), and viscosities (flowable and sculptable). Microhardness test was conducted on top and bottom surface using Vickers microhardness tester and DOC was calculated as the bottom/top ratio of yielded scores. Statistical analysis was done using a Mann Whitney test at p< 0.05. Results: DOC ranged between 52-95%. FBF composite exhibited the lowest overall hardness numbers. At 2-mm thickness, all the samples achieved an appropriate DOC. However, at 4mm thickness, only the light shades for FBF and TNF samples achieved a DOC very close to 0.8. At 4-mm thickness, the light shades for FBF, TNF and FZ samples exhibited significantly higher DOC compared to dark shades. For 4-mm-thick samples, the DOC of FiltekTM Bulk Fill (dark and light shades (and the DOC of Tetric® Bulk Fill (light shade (were different in flowable type from the sculptable type. Conclusion: The shade and the viscosity of bulk-fill composites influence their DOC at 4-mm depths. Moreover, 20 seconds of light curing appears insufficient for 4mm thickness of bulk-fill composite.